Pengaruh NPL dan Inflasi terhadap ROA Pada Bank BUMN Yang Terdaftar Di BEI Periode 2013 - 2023 - Anggraeni, Khaerunisa Suci; Syarief, Moch. Edman (Program Studi Perbankan dan Keuangan Fakultas Ekonomi Universitas Siliwangi, 2024)
Return On Asset (ROA) is the bank's capabillity to obtain profits from the sale or use of its assets, but the ROA metric can be affected by numerous variables, specifically, aspect originating from within and outside. One of the internal aspect that can alter ROA is credit, in credit distribution there are often non-performing loans that can affect bank revenue. Another external factor is inflation which will result in bank’s profitability value to growth or decrease. Therefore, This research aims to examine how non-performing loans and inflation impact ROA. The study focuses on state-owned banks listed on the IDX over a ten-year periode from 2013 – 2023. The study employs multiple linear reggresion as the primary method for data analysis. The findings of this investigation are derived from application of this stactical technique, the result reveal that NPL partially affected ROA and Inflation partially affected ROA. Likewise, NPL and Inflation simultaneously affect ROA.